Palaeoenvironmental reconstructions during the Meso- to Neolithic transition (9.2–5.3 cal. ka BP) in Northwestern France: Palynological evidences. (March 2019) - Lambert, Clément; Vidal, Muriel; Penaud, Aurélie; Le Roy, Pascal; Goubert, Evelyne; Pailler, Yvan; Stephan, Pierre; Ehrhold, Axel
Sedimentological, palynological, and micropalaeontological studies carried out throughout the first half of the Holocene, during the Mesolithic/Neolithic transition in the Bay of Brest (i.e. 9200–9000 and 6600–5300 cal. BP) and in the Bay of Douarnenez (i.e. 9200–8400 cal. BP), allowed characterizing coastal environmental changes under the increasing influence of the relative sea-level rise. The gradual flooding of the two studied sites implied a transition from river valleys to oceanic bays as revealed by the gradual retreat of salt marsh environments, as detected through palynological analysis. In addition, these high-resolution studies highlight the regional imprint of the North Atlantic millennial climate variability in north-western coastal environments. Two cold climate events are indeed suggested to have been locally marked by a moisture increase, mainly detected by increases in Lingulodinium machaerophorum, Corylus, and Alnus percentages at 8550 cal. BP in the Bay of Douarnenez and at 6250 cal. BP in the Bay of Brest. Moreover, regarding the Neolithic transition timing in the Bay of Douarnenez, large pollen grains of Poaceae (i.e. Cerealia -type pollen grains) have been detected at around 8600 cal. BP, that is, 1500 years before the general accepted cereal cropping appearance in Western France. These results, consistent with other palynological studies conducted in the French Atlantic coast, could underline a Mesolithic 'proto-agriculture' in Brittany.